Feasibility of establishing a core set of sexual, reproductive, maternal, newborn, child, and adolescent health indicators in humanitarian settings: results from a multi-methods assessment in the Democratic Republic of Congo - Emina, Jacques; Etinkum, Rinelle; Aissaoui, Anya; Gbomosa, Cady N.; Elamurugan, Kaeshan; Rajendra, Kanya L.; El Mowafi, Ieman M.; Kobeissi, Loulou (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Reliable and rigorously collected sexual, reproductive, maternal, newborn, child, and adolescent health (SRMNCAH) data in humanitarian settings are often sparse and variable in quality across different humanitarian settings, and there is a lack of consensus about a core set of indicators that humanitarian actors including national health systems should report on. To address this gap in quality data, the World Health Organization (WHO) developed a core set of indicators for monitoring and evaluating SRMNCAH services and outcomes and assessed their feasibility in four countries, including the Democratic Republic of Congo (DRC) with the goal of aggregating information from global consultations and field-level assessments to reach consensus on a set of core SRMNCAH indicators among WHO partners. Methods The feasibility assessment in the DRC focused on the following constructs: relevance/usefulness, feasibility of measurement, systems and resources, and ethical issues. The multi-methods assessment included five components; a desk review, key informant interviews, focus group discussions, facility assessments, and observational sessions. Results The findings suggest that there is widespread support among stakeholders for developing a standardized core list of SRMNCAH indicators to be collected among all humanitarian actors in the DRC. There are numerous resources and data collection systems that could be leveraged, built upon, and improved to ensure the feasibility of collecting this proposed set of indicators. However, the data collection load requested from donors, the national government, international and UN agencies, and coordination/cluster systems must be better harmonized, standardized, and less burdensome. Conclusions Despite stakeholder support in developing a core set of indicators, this would only be useful if it has the buy-in from the international community. Greater harmonization and coordination, alongside increased resource allocation, would improve data collection efforts and allow stakeholders to meet indicators’ reporting requirements.

Plain Language Summary In humanitarian settings, data collection is often unreliable and not standardized—especially with regards to sexual, reproductive, maternal, newborn, child, and adolescent health (SRMNCAH). In order to address this gap in data quality, the World Health Organization proposed a list of core indicators to four countries, including the Democratic Republic of Congo (DRC). The goal was to use the findings from the DRC context to contribute to the determination of a core set of indicators. This study had two components: a feasibility assessment and a multi-methods assessment. The feasibility assessment in the DRC focused on the relevance of the proposed indicators, the feasibility of measurement, the resources in place, and ethical issues. The multi-methods assessment included a desk review, interviews with key informants, and focus groups and facility assessments. The findings showed that partners in the DRC supported developing a standard set of SRMCAH indicators that can be used among all humanitarian partners in the country. There are many systems in place that could be used or strengthened to improve data collection. However, the findings also showed that there must be better collaboration and coordination between the different partners in the DRC, as well as increased resources, to alleviate burden on frontline staff. In conclusion, though there is a desire to harmonize indicators, more input and resources are needed from the international community to aid in the standardization of data collection in order to meet local reporting requirements and ease burden on local staff.